Taxi drivers' attitudes toward road safety in Pakistan. Issue 6 (June 2015) - Rehman, A.; Imran, S.; Hassan, M.; Akhlaq, A.; Iqbal, S.; Beg, F.; Zahid, G.; Khalid, H.; Qadir, F.S.; Murad, H.F.; Baloch, N.U.A.; Awais, M.; et al.
Highlights Taxi drivers represent a vulnerable group of road users, who are at an increased risk of motor vehicle crashes. Most taxi drivers included in this study did not use seatbelts regularly. One-third of taxi drivers were driving illegally, which suggests a lapse in the implementation of road safety regulations. One-fourth of taxi drivers were sleeping for less than 7 h a day, which may increase the risk of motor vehicle crashes.